Zinc treatment in the contagians agalactia of sheep and goats - ΤΣΙΓΓΑΡΙΔΑΣ Κ. (Journal of the Hellenic Veterinary Medical Society, 2019)
Experiments were carried out on the use of zinc as a preventive and therapentic agent against the Contagious Agaiaxia of sheep. The results show the bénéficient effect of zinc in both cases. The favorable effect of zinc appears three days after its administration. Zinc dosing to healthy animals could be used as a prophylactic mesure. The indicate doses zinc either in the prevention or treatment are not toxic